Analysis of Friction Stir Welds. Part I: Transient Thermal Simulation Using Moving Heat Source - Doos, Qasim M. (Nahrain University College of Engineering Journal, 2008)
This paper describes the first part of the development of a non-linear finite element simulation of the friction stir welding process; it is concerned with thermal analysis. A transient, three dimensional, non-linear thermal model with moving heat source was developed. Also a steady-state, three dimensional, non-linear fluid-thermal model with stationary heat source was developed. Differences of results for both models were discussed. Results of both models werecompared with experimental work. Transient thermal model results appear to be more reliable as compared to the CFD approach.